Local and regional politicians’ considerations of newly arrived migrants’ health in political decision-making : a public health study in northern Sweden - Svanholm, Sara; Carlerby, Heidi; Viitasara, Eija (Journal of Public Health, 2023)
Background and aim: Early action is important for promoting newly arrived migrants’ health. Politicians are major actors in decision-making that affects health outcomes in the population. Therefore, the aim of this study was to explore local and regional politicians’ considerations of newly arrived migrants’ health in political decision-making: whether politicians reflect on or discuss the effects of decision-making specifically on newly arrived migrants’ health, whether considerations differ between municipality and regional politicians, and how knowledge and attitudes are associated with such considerations. Subject and methods: A cross-sectional quantitative study was conducted. A total of 667 municipality and regional politicians from northern Sweden responded to a questionnaire developed based on interviews with politicians. Bivariate analyses were performed using χ2 tests, the independent samples t-test, and the Wilcoxon signed-rank test. Multivariate analysis was performed using binary logistic regression. Results: Politicians considered the effects on newly arrived migrants’ health significantly less frequently than those on the total population’s health. Regional politicians discussed such effects more often than municipality politicians. Knowledge (odds ratio [OR] = 1.343), attitude (OR = 5.962), previous experience working on public health issues (OR = 1.784), and female gender (OR = 1.787) were positively associated with considering effects on newly arrived migrants’ health in decision-making. Conclusion: Politicians play important roles in health promotion, and most consider health-related effects in their decision-making. However, about a third do not consider such effects. General health-related knowledge and attitude are important factors that could be affected or changed during political assignments.